Features of patients with premature ventricular complex ablation: single center case series - Tutuncu, Ahmet; Yılmaz, Erhan (The European Research Journal, 2021)
Objectives: In patients who do not respond to medical treatment with idiopathic premature ventricular complex (PVC), catheter ablation is performed using the electroanatomic mapping (3D EAM) system for ablation. The aim of this study is to evaluate the acute and long-term success of patients and the procedural features and complication results associated with PVC localization in patients who underwent catheter ablation in our center. Methods: Two hundred seventeen patients who underwent activation mapping and ablation using 3D EAM for PVC were included in the study. Patients were followed up for acute procedure success, periprocedural complications, and six-month long-term recurrence. In addition, these parameters, PVC’s were evaluated in three groups as right ventricular outflow tract (RVOT), coronary cusp and rare localized origin, and clinical outcomes and interventional variables related to the success of the PVC’s location were compared. Results: In our study, the mean age of the patients was 43 ± 12.1 years and the female gender ratio was 37.8%. When catheter ablated PVC foci were evaluated, it is seen that 81 (37.3%) were from RVOT and 56 (25.8%) were from coronary cusp. In addition, 6 (2.8%) were aortomitral continuity, 22 (10.1%) were left ventricular summit/epicardial, 17 (7.8%) were parahisian, and total 80 (36.8%) were rare localized PVCs. Acute procedure success was 92.6% and long-term procedure success was 83% in all cases. When the patients in our study were analyzed according to their PVC locations and procedure successes, those with rare localization compared to those with RVOT and coronary cusp origin were 66 (87.5%), 79 (96.3%), and 53 (94.6%); respectively (p = 0.03) and long-term successes were 58 (72.5%), 73 (90.1%), and 49 (87.5%); respectively (p < 0.05). Long-term transaction success was lower. Conclusions: Frequent PVCs can be treated with electroanatomic mapping and radiofrequency ablation with high success rate and low complication rate. Patients with RVOT and coronary cusp-derived PVC had a high acute and long-term success rate, while success rates were lower in rare localized PVCs from epicardial/summit, papillary muscle, parahisian and tricuspid-mitral anulus.